Can teacher education programs help prepare new kindergarten and first grade teachers to address student absenteeism?. (December 2020) - Gottfried, Michael; Jacob Kirksey, J.; Hutt, Ethan
Highlights: We examine new teachers' roles in addressing students' absences. For K-1, teachers better understood absenteeism based on their preparation. There are null findings for teachers in grades 2–5. Abstract: Children in kindergarten and first grade are missing more school than at any other point during the elementary years. While some research has examined what schoolwide programs might help to reduce absences, limited work has focused on the role of teachers. We are the first known study to examine kindergarten and first grade teachers, and none have done so vis-à-vis teacher preparation. We collected statewide data on elementary school teachers graduating from teacher preparation programs in the 2017–18 year in California. For teachers entering kindergarten or first grade classrooms, we find that kindergarten and first grade teachers had a greater perceived understanding of chronic absenteeism when they perceived their licensure requirement and placements as being helpful in preparing to teach. We also find that teachers felt better prepared to address absenteeism when they felt stronger support from their university supervisors. In contrast, there are null findings for new teachers entering second through fifth grade classrooms. This is meaningful given that teachers who feel the most prepared are entering classrooms where students are the most likely to be absent. Implications are discussed.